Implementasi Sistem Informasi Berbasis Web untuk Optimalisasi Operasional pada UMKM Krupuk Singkong Nusantara Putra - Shinta Nilam Sari Muslim; Firman Nurdiyansyah; Adryan Syah (Pusat Riset dan Inovasi Nasional, 2024)
Krupuk Singkong Nusantara Putra, a small business in Batu, East Java, faced challenges in adopting information technology for operational efficiency and market reach. This study aimed to develop a web-based information system using the Waterfall model to enhance their operations. The system was designed to be user-friendly, maintainable, and integrated with WhatsApp for customer interactions. Development involved setting up WordPress, customizing themes, adding necessary plugins, and creating functional pages. Testing confirmed the system's functionality, security, and performance. The implementation improved administrative efficiency and product management. Regular maintenance and employee training are recommended to ensure optimal performance and adaptation to dynamic needs. Future research should involve comprehensive needs analysis and broader stakeholder engagement.